PEMILIHAN BAHAN PEMULIAAN PADI UNTUK PEMBENTUKAN VARIETAS UNGGUL DISKRIMINATIF TUMPANGSARI: PADI + JAGUNG + UBIKAYU DI LAHAN KERING. I. HASIL TANAMAN PADI - Abdul Bari; Zainuddin Harahap; S. Sudiatso; Khairil Anwar (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
Intercropping of Maize, Rice and Cassava is commonly practiced by subsistent farmers on upland agriculture in Indonesia. In general, grain yield of rice under intercropping is very much lower than under monoculture crop. This due to the fact that the variety of rice planted under intercrop was breed and selected under elite, monoculture crop condition. Field experiment to screen rice breeding materials planted in association with maize and cassava were carried out in Pekalongan (Lampung), October 1993 - November 1994. Three out of 29 entries of rice were selected, EO2 (B6136-Tb-0-1-5), E20 (Tb47h-Mr-17) and E22 (Tb154c-Tb-1). Performance test on grain yield relative stability for selected materials have to be done, before practicing any form of improvement by means of selection.